A Hebrew Exegesis Of Isaiah 62:1-5 The Restoration Of Zion - Philip Suciadi Chia; Juanda Juanda (Theological Journal Kerugma, 2019)
In this study, spiritual, social-ethic and political background will be scrutinized to assist to understand Isaiah chapter 62 comprehensively. Spiritual life of God’s people is declined in the book of Isaiah because of idolatries and nations. Hebrew people make idols out of trees and worship pagan wooden idols (40:18-20; 44:9-20). Isaiah employs prophetic images for the covenant-breaking idolatry and worship of other gods by adultery and illicit sexual intercourse. It is clear that Isaiah is not exclusively interested in the interpersonal and social relationship structures within Israel. He is also concerned with the broader canvas of international politics.